Pentingnya Menjadi Pemilih Cerdas Menuju Pemilu Berkualitas dan Berintegritas Pada Pemilu 2024 - Eva Susanti; Aldi Setiawan; Nabila Aisyah; Tia Oktafiani Putri; Vikka Rosdiana Nova; Opi Ismarita (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Elections are indicators or benchmarks in a democratic country. The means of sovereignty are realized in the form of citizens' voting rights, a general election that is based on direct, general, free, secret, honest and fair purposes to elect leaders who will continue the previous leadership relay with the aim of continuing, managing government administration and serving all levels of society. Voters have a big role in Indonesia's leadership in the upcoming 2024 election. If the wrong leader is chosen, it can result in the destruction of the nation and state. The method used in this socialization activity is as follows: (1) the lecture method is used to explain material related to "the importance of being an intelligent voter in realizing quality and integrity elections in the 2024 election. (2) the discussion method is used to deepen the discussion material with questions and answers delivered to socialization participants. (3) the method of pre-test and post-test questions to determine the increase in participants' understanding before and after socialization. This socialization activity was located in the UBR 31 classroom, the government science study program, the faculty of social sciences and political science. The result of this socialization activity is that students as socialization participants are more aware of the importance of being smart voters to realize elections of quality and integrity in the 2024 elections.